2019
DOI: 10.1098/rspb.2019.1319
|View full text |Cite
|
Sign up to set email alerts
|

Contextual priors do not modulate action prediction in children with autism

Abstract: Bayesian accounts of autism suggest that this disorder may be rooted in an impaired ability to estimate the probability of future events, possibly owing to reduced priors. Here, we tested this hypothesis within the action domain in children with and without autism using a behavioural paradigm comprising a familiarization and a testing phase. During familiarization, children observed videos depicting a child model performing actions in diverse contexts. Crucially, within this phase, we implicitly biased action-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 52 publications
1
49
1
Order By: Relevance
“…Accordingly, reduced reliance on prior expectations relative to sensory inputs has been shown to lead to a plethora of abnormalities consistently observed in ASD individuals [21,22]. In a similar vein, although the ability to read the goal of an action during action observation seems to be preserved in ASD ( [23], but see also [24,25] for contrasting results), there is consistent evidence that, when the outcome of the action is ambiguous, individuals with ASD exhibit impairments in using contextual priors to predict action unfolding [20,[26][27][28]. Collectively, these observations highlight the difficulties of ASD individuals in integrating the available sensory evidence with previous experience when dealing with the prediction of both physical and social stimuli.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Accordingly, reduced reliance on prior expectations relative to sensory inputs has been shown to lead to a plethora of abnormalities consistently observed in ASD individuals [21,22]. In a similar vein, although the ability to read the goal of an action during action observation seems to be preserved in ASD ( [23], but see also [24,25] for contrasting results), there is consistent evidence that, when the outcome of the action is ambiguous, individuals with ASD exhibit impairments in using contextual priors to predict action unfolding [20,[26][27][28]. Collectively, these observations highlight the difficulties of ASD individuals in integrating the available sensory evidence with previous experience when dealing with the prediction of both physical and social stimuli.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, in the visual domain, prior contextual information is responsible for the elementary regularities that bias our perception of shape and color [18] as well as for the effects of perceptual learning on the processing of visual objects [19]. Moving to the framework of social cognition, studies challenging the comprehension of social behavior showed that individuals with typical development strongly rely on prior knowledge regarding the context in which actions are usually observed in order to recognize action unfolding [13][14][15][16], especially when perceptual information is scarce [20]. The predictive coding account may explain the perceptual impairments of ASD individuals in both the social and non-social domains.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, the evidence for these theories is still sparse and the idea of a global "predictive impairment [...] shared across individuals" (Sinha et al [16]) seems to be contradicted by an absence of apparent deficits in motion prediction of objects (Tewolde et al [23]), predictions about the weight of objects based on material cues (Arthur et al [24]) and other cognitive processes supposed to tap into predictive abilities (Croydon et al [25], Manning et al [26], Cruys et al [27], Maule et al [28]). Where group differences have been found, they mostly pertain to predictive deficits in the social domain: Balsters et al [29], Chambon et al [30], Turi et al [31], Amoruso et al [32], von der Lühe et al [33], but this is not universally true, as Pell and colleagues have found no deficits in prediction-based perception of other people's gaze direction (Pell et al [34]).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-and post-training evaluation sessions in the "sweet" stand scenario are administered to both the experimental and the control groups. The paradigm exploits a probabilistic design that has already shown its reliability in assessing social prediction abilities, since children with Autism Spectrum Disorder (ASD), who show clinically relevant social deficits, were impaired in using contextual priors to predict the unfolding intention of observed actions ahead of realization (45). Within a session, events take place in a pseudorandom way in respect to the pre-established probabilities.…”
Section: Evaluation Sessionsmentioning
confidence: 99%
“…In other words, the paradigm that underlies our applications should specifically enhance the building of predictive internal models of others' behaviour. Since a lack of this computation has been proposed to explain social deficits in cerebellar patients (15,31) as well as in autism (45), boosting the building of internal models of other's intention could improve social prediction with a likely impact on more general social cognition abilities.…”
Section: Introductionmentioning
confidence: 99%